Relationship between pediatric liquid medicines (PLMs) and dental caries in chronically ill children - Goyal, Ankita; Rani, Vatchala; Manjunath, Bhadravathi Cheluvaiah; Rathore, Kanupriya (Padjadjaran Journal of Dentistry, 2019)
Introduction: Purpose of this research is to assess the relationship between long-term pediatric liquid medicines (PLMs) consumption and dental caries in 2–12-years-old chronically ill children. Methods: A cross-sectional study was performed in a public pediatric hospital in India for a period of 6 months. A total of 455 children aged 2–12 years old with various chronic diseases who were receiving PLMs for more than 6 months were selected as the subjects in this study and compared with 531 children of similar age group and diseases who received other forms of medication. Dental caries was measured by DMFT/dmft and data collected were analyzed with SPSS (17th version) using statistical tests such as t-test and one-way ANOVA. Univariable logistic regression was used where the significance was fixed at a a p value of less than 0.001. Results: Children on PLMs had an increased risk of dental caries than those on other forms of medications (OR: 3.142, 95% CI: 2.37–4.15, p < 0.001). The prevalence of dental caries was higher (77.8%) in children consuming PLMs when compared to other forms of medication (52.7%). The mean DMFT and dmft scores were significantly higher in the study group when compared to the control group (p = 0.001). Conclusion: Long-term consumption of pediatric liquid medicines containing sucrose as a risk factor for dental caries among chronically ill children. sugar free options has to be used during prescription to prevent medication-triggered caries.Keywords: Paediatric liquid medicine, medication-triggered caries, sugar-free medication